(untitled) (CIPEEX, 2025)
REVIVE is a software engineering project focused on helping users overcome addictions such as smoking, gambling, eating disorders, and technology use. According to the latest global estimates, around 5.5% of the population aged between 15 and 64 has used drugs at least once in the past year, while 36.3 million people, or 13% of the total number of people who use drugs, suffer from drug use disorders.From this perspective, the app offers key features like an interactive calendar for tracking daily progress and relapses, and support for managing multiple addictions simultaneously. It also includes a community tab for users to share experiences and gain mutual support, as well as access to healthcare professionals for guidance. REVIVE aims to promote personal goal tracking, engagement, and a supportive environment to assist users in achieving lasting lifestyle changes.